2013
DOI: 10.1021/cs400551g
|View full text |Cite
|
Sign up to set email alerts
|

Partial Deoxygenation of Glycerol Catalyzed by Iridium Pincer Complexes

Abstract: Iridium pincer complexes (POCOP)Ir(CO) (POCOP = κ 3 -C 6 H 3 -1,3-[OP( t Bu) 2 ] 2 ) and substituted POCOP derivatives catalyze deoxygenation of glycerol to npropanol and 1,3-propanediol in good yield under moderate conditions (acidic aqueous dioxane, 200 °C, 80 bar H 2 ). Catalyst solubility in the polar reaction mixture is improved by incorporation of a polar moiety in the para position of the POCOP phenyl ring, with the best results obtained with a dimethylamino substituent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 26 publications
5
57
2
Order By: Relevance
“…We previously reported the five coordinate complex [ (tBu)4 (POCOP)­Ir­(CO)­(H)]­BArF 20 ( 1 ) [BArF 20 = B­(C 6 F 5 ) 4 ] and reported our failure to observe coordination of hydrogen (under 8 atm of H 2 ) to the open site trans to the iridium–hydride . Additionally, we found that low temperature protonation of the Ir­(III) trans -dihydride (tBu)4 (POCOP)­Ir­(CO)­(H) 2 gave rapid evolution of hydrogen . We were unable to directly detect the dihydrogen complex which is proposed as an intermediate in the mechanism for our Ir catalyzed glycerol deoxygenation …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…We previously reported the five coordinate complex [ (tBu)4 (POCOP)­Ir­(CO)­(H)]­BArF 20 ( 1 ) [BArF 20 = B­(C 6 F 5 ) 4 ] and reported our failure to observe coordination of hydrogen (under 8 atm of H 2 ) to the open site trans to the iridium–hydride . Additionally, we found that low temperature protonation of the Ir­(III) trans -dihydride (tBu)4 (POCOP)­Ir­(CO)­(H) 2 gave rapid evolution of hydrogen . We were unable to directly detect the dihydrogen complex which is proposed as an intermediate in the mechanism for our Ir catalyzed glycerol deoxygenation …”
Section: Resultsmentioning
confidence: 86%
“…We previously showed that (tBu)4 (POCOP)­Ir­(CO) [ (tBu)4 (POCOP) = κ 3 -C 6 H 3 -2,6-(OP­( t Bu) 2 ) 2 ] complexes could selectively catalyze the deoxygenation of glycerol to 1,3-propanediol and 1-propanol . The former is a useful precursor for the production of polyesters, and the latter is a potential fuel building block .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Carbon monoxide has been long known to coordinatively add to both PC(sp 2 )P- 15 and PC(sp 3 )P-supported 16 iridium(III) complexes, and such iridium carbonyl complexes have later been found to be involved in catalytic transformations such as transfer hydrogenations of ketones 8 and olen hydroformylation. 17 PCP iridium(I) carbonyl complexes are well known for benzene based pincer structures, 7,[18][19][20][21][22] and have been reported to catalyse the decarbonylation of 2-naphtaldehyde 23 and the partial deoxygenation of diols 24 and glycerol, 25 but there are no PC(sp 3 ) P-supported iridium(I) carbonyl complexes reported to this date.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore over-hydrogenolysis to propanols and even propane can proceed over the catalysts that can work by the dehydration + hydrogenation route. Homogeneous Ru and Ir complexes combined with external acid are typical catalysts for production of propanols or propane from glycerol [10,11] and 1,2-PrD [12][13][14]. In contrast, under more basic conditions over heterogeneous metal catalysts, the dehydrogenation + dehydration + hydrogenation route is preferred to the dehydration + hydrogenation route.…”
Section: Conventional Hydrogenolysis Of Glycerol and Tetrahydrofurfurmentioning
confidence: 99%